Teacher Participation in School Budge Administration in Mueang Sa Kaeo District, under The Office of Sakaeo Primary Educational Service Area 1 - มณีรัตน์ พิพัฒน์; รักษนคร กุลจิรา (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research aimed to: 1) examine the level of teachers’ participation in budget administration in schools in Mueang Sa Kaeo District; 2) compare teachers’ participation in budget administration as classified by gender, educational level, and work experience; and 3) explore guidelines for developing teachers’ participation in budget administration in schools under the Sa Kaeo Primary Educational Service Area Office 1. The sample consisted of 237 teachers in the 2025 academic year, determined using the Krejcie and Morgan (1970: 608) table. Stratified sampling and simple random sampling techniques were employed. The research instrument was a five-point rating scale questionnaire with an Index of Item-Objective Congruence (IOC) ranging from 0.60 to 1.00 and a reliability coefficient of 0.92. Data were analyzed using frequency, percentage, mean, standard deviation, independent samples t-test, F-test, and Scheffé’s method for multiple comparisons. The findings revealed that the overall and aspect-wise levels of teachers’ participation in budget administration were at a high level. When classified by gender, there was a statistically significant difference at the .05 level in overall participation, particularly in financial management and budget control, as well as financial reporting and performance reporting. In terms of educational level, no significant differences were found in overall or aspect-wise participation. Regarding work experience, no significant difference was found in overall participation; however, some aspects showed statistically significant differences at the .05 level. Guidelines for enhancing teachers’ participation in school budget administration should emphasize participatory management by encouraging teachers to be involved in all stages, including analysis, planning, implementation, monitoring and evaluation, and reporting. This approach is expected to improve efficiency, transparency, and cost-effectiveness in school budget administration.